Analysis Of The Effect of The Number Of Recipients of Social Assistance From The Government on The Macroeconomic Indicators of Cirebon City - Kartini, Nuri (Jurnal Ekuisci, 2025)
Background. DTKS is Integrated Social Welfare Data that includes Social Welfare Service Providers (PPKS), Recipients of Assistance, and Potential Sources of Social Welfare (PSKS). DTKS contains 40% of the population with the lowest social welfare status. The government, in this case, the Ministry of Social Affairs of the Republic of Indonesia, uses DTKS to determine who is entitled to social assistance issued by the government. Aim. This research aims to determine the influence of the benefits of DTKS, in this case, the Number of Recipients and the Number of Social Assistance Recipients from the Government from the Government on macroeconomic indicators in Cirebon City. Methods. From the results of the study using a descriptive analysis approach and a linear regression model Result. Meanwhile, judging from the magnitude of the variant, the highest presentation was obtained, namely the influence between the number of Social Assistance recipients from the Government on the 6 Macroeconomic Indicators of Cirebon City less than 41%, which is 2.29% to 40.5% and around 59% is influenced by other factors that are not researched. Conclusion. It can be concluded that from the Significant Value, there is no significant influence between the Number of Social Assistance Recipients from the Government on the 6 Macroeconomic Indicators of Cirebon City. Implementation. The next researcher, the Regional Research, Development and Statistics government, and the Yogyakarta Regional Development Planning Agency can make suggestions based on this study's conclusion.